Successful Transposition of Lesson Study A Knowledge Management Perspective - Cheng, Eric C. K.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2019)
This book analyses the organisation cultures that promote Japanese Lesson Study, identifies the soul of lesson study, which is missing in other cultures, and discusses the conditions for successfully transplanting the Lesson Study to other cultures. Adopting Nonaka and Tateuchi$1 (Bs (1995) SECI knowledge creation model as the analytical lens, it explores the tacit and explicit knowledge convention and creation processes in lesson study. Unpacking the mechanism of the knowledge management process and practices could assist policy makers and school administrators, educators in contextualising lesson study to their school systems. The book provides an accessible discussion of the benefits and challenges of introducing lesson study, and presents three new research dimensions to analyse it: reviewing the historical development of lesson study in terms of the pendulum swings between professional accountability and state accountability in developing the school-based curriculum and the national curriculum; examining lesson study as a knowledge management tool for creating pedagogical knowledge for curriculum implementation: and studying the (3z(Bkaizen kata(3y (Bembedded in the PDCA cycles of lesson study as an organization routine for school improvement.s
1 Conceptualising Lesson Study from International Literature -- 2 Reconceptualising Lesson Study as Knowledge Management -- 3 Applying SECI Model for Creating Pedagogical Knowledge -- 4 Rotating PDCA Cycles through SECI Processes for Curriculum Management -- 5 Institutionalizing Lesson Study for Managing Knowledge.
Keywords: Learning; Instruction; Knowledge management; Curriculums (Courses of study).; Education$1 (BCurricula.s; Learning & Instruction; Knowledge Management; Curriculum Studies